Germline Compound Heterozygous Variants Identified in the STXBP2 Gene Leading to a Familial Hemophagocytic Lymphohistiocytosis Type 5: A Case Report - Vera Maria Dantas; Cassandra Teixeira Valle; Roberta Piccin de Oliveira; Mylena Taíse Azevedo L. Bezerra; Cleia Teixeira do Amaral; Raissa Anielle S. Brandão; Jussara M. Cerqueira Maia; Tirzah Braz Petta (Frontiers Media S.A., 2021)
Familial hemophagocytic lymphohistiocytosis (FHL) is a rare, potentially fatal autosomal-recessive immunodeficiency, and STXBP2 mutations have been associated with FHL type 5 (FHL-5). Here, we report a case of a 2-year-old boy who presented with recurrent fever, hepatosplenomegaly, pancytopenia, hyperferritinemia, and hypofibrinogenemia since 4 months of age. His genetic analysis revealed a compound heterozygosity of the STXBP2 gene with a described pathogenic mutation, c.1247-1G>C (splicing acceptor site), harbored by his father and a likely pathogenic variant of uncertain significance (VUS), c.704G>A (p.Arg235Gln), harbored by his mother. He was diagnosed as compound heterozygous for FHL-5 and was treated with the HLH-2004 protocol. Since treatment, this patient has been in remission, and he is being evaluated for a hematopoietic stem cell transplantation (HSCT).